Investigation into the role of the cholinergic system in radiation-induced damage in the rat liver and ileum - ERCAN, FERİHA; ŞENER, GÖKSEL; GÖREN, MEHMET ZAFER (OXFORD UNIV PRESS, 2014)
It has been previously shown that acetylcholine (ACh) may affect pro-inflammatory and anti-inflammatory cytokines. The role of the cholinergic system in radiation-induced inflammatory responses and tissue damage remains unclear. Therefore, the present study was designed to determine the radio-protective properties of the cholinergic system in the ileum and the liver of rats. Rats were exposed to 8-Gy single-fraction whole-abdominal irradiation and were then decapitated at either 36 h or 10 d post-irradiation. The rats were treated either with intraperitoneal physiological saline (1 ml/kg), physostigmine (80 mu g/kg) or atropine (50 mu g/kg) twice daily for 36 h or 10 d. Cardiac blood samples and liver and ileal tissues were obtained in which TNF-alpha, IL-1 beta and IL-10 levels were assayed using ELISA. In the liver and ileal homogenates, caspase-3 immunoblots were performed and myeloperoxidase (MPO) activity was analyzed. Plasma levels of IL-1 beta and TNF-alpha increased significantly following radiation (P < 0.01 and P < 0.001, respectively) as compared with non-irradiated controls, and physostigmine treatment prevented the increase in the pro-inflammatory cytokines (P < 0.01 and P < 0.001, respectively). Plasma IL-10 levels were not found to be significantly changed following radiation, whereas physostigmine augmented IL-10 levels during the late phase (P < 0.01). In the liver and ileum homogenates, IL-1 beta and TNF-alpha levels were also elevated following radiation, and this effect was inhibited by physostigmine treatment but not by atropine. Similarly, physostigmine also reversed the changes in MPO activity and in the caspase-3 levels in the liver and ileum. Histological examination revealed related changes. Physostigmine experiments suggested that ACh has a radio-protective effect not involving the muscarinic receptors.
Keywords: IL-1 beta; IL-10; TNF-alpha; myeloperoxidase activity; caspase-3; MONONUCLEAR LEUKOCYTES; OXIDATIVE STRESS; UP-REGULATION; CYTOKINES; ACETYLCHOLINE; IRRADIATION; APOPTOSIS; RADIOTHERAPY; RECEPTOR; INJURY